KAJIAN FAKTOR PENYEBAB KENDALA IMPLEMENTASI KONSEP GREEN CONSTRUCTION PADA GEDUNG PASAR GIANYAR - NI LUH MADE AYU MIRAYANI PRADNYADARI; TJOKORDA ISTRI PRAGANINGRUM (Universitas Mahasaraswati K. Mataram, 2023)
Ongoing construction projects using material resources and equipment can harm environmental conditions. Thus, it requires high awareness and willingness to maintain the environment in construction project management. Green construction is explained as an effort or strategy for managing construction activities, including the use of resources that are efficient and environmentally friendly so that they can support a sustainable movement. This research aims to discover the causes of obstacles in implementing green construction in the Gianyar Market development project. The method used is qualitative, with interviews with 28 respondents involved in the construction process of the Gianyar Market development. From the results of the study, it was found that the constraints experienced by contractors in the implementation of Greem construction included (1) Human Resources, (2) Materials or Material Resources, (3) Facilities and Infrastructure, and (4) Costs. These constraints are caused by several factors, namely (1) Lack of understanding, (2) Requiring particular experts, (3) Need to improve the quality of facilities and infrastructure, and (4) Readiness of the budget. From these results, it is possible to evaluate and increase the quantity and quality of the facilities and infrastructure owned to support the implementation of green construction, as well as coordinate with Experts who understand green construction well.